Strategies for Enhancing Human Resource Capacity to Support Digital Transformation in Pejala Village, Penajam District, Penajam Paser Utara Regency, East Kalimantan - Irmayani; Hasniaty; Sadly Abdul Jabbar (GoodWill, 2026)
This study aims to describe strategies for enhancing human resource (HR) capacity in supporting digital transformation, as well as to identify the obstacles and challenges encountered in its implementation in Pejala Village, Penajam District, Penajam Paser Utara Regency. The research was conducted at the Pejala Village Office using a descriptive qualitative approach. Data were collected through interviews, observation, and documentation, and were then analyzed thematically to obtain an in-depth understanding of the phenomenon under study. The findings reveal that strategies to enhance HR capacity were carried out through training, technical guidance, performance evaluation, utilization of digital applications, and support from the Department of Communication and Informatics. These efforts not only strengthened the skills of local officials but also encouraged the integration of digital-based public service systems that are faster, more efficient, and more accurate. However, several challenges remain, including limited competence of officials in operating technology, unstable internet networks, limited digital devices, low digital literacy among the community, and restricted village office budgets. These findings indicate that although digital transformation in Pejala Village has begun to progress well, the process still requires more targeted policy strengthening, adequate technological infrastructure provision, and continuous training based on the needs of local officials. Thus, digital transformation at the village level has the potential to support the improvement of public service quality to be more responsive, transparent, and accountable.